Impact of InxGa1-x composition and source Zn diffusion temperature on intrinsic voltage gain in InGaAs TFETs - Bordallo, C.; Martino, J.; Agopian, P. [UNESP]; Alian, A.; Mols, Y.; Rooyackers, R.; Vandooren, A.; Verhulst, A.; Simoen, E.; Claeys, C.; Collaert, N.; Thean, A. (Institute of Electrical and Electronics Engineers (IEEE), 2017)
This work reports for the first time on the experimental study of the intrinsic voltage gain of InGaAs nTFET. The influence of Indium/Gallium composition and Zn diffusion temperature is analyzed. For a higher Indium amount (In0.7Ga0.3As compared to In0.53Ga0.47As) the band to band tunneling (BTBT) is improved due to bandgap narrowing. A higher Zn diffusion temperature gives rise to a higher source doping, resulting in a smaller tunneling length, which also increases BTBT. In both devices the intrinsic voltage gain is improved. One interesting characteristic of these devices is that they present good analog performance at low voltages (VGS=VDS=0.6V), which is promising for low power/low voltage analog applications. High-temperature operation increases in all cases more the output conductance than the transconductance, resulting in a lower intrinsic voltage gain.
Keywords: Analog; III-Vmaterials; Temperature effects; TFET